2013
DOI: 10.1080/09540121.2013.764387
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure behaviour and experienced reactions in patients with HIV versus chronic viral hepatitis or diabetes mellitus in Germany

Abstract: Disclosure is a prerequisite to receive disease-specific social support. However, in the case of a stigmatised disease, it can also lead to discrimination. We aimed to assess disclosure rates of HIV patients and the reactions they encountered in comparison to patients with chronic viral hepatitis or diabetes mellitus and patients' general perception of disease-specific discrimination. We constructed a self-report questionnaire, anonymously assessing the size of the social environment, the persons who had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Patients' baseline data, rate of disclosure and support experiences in detail are published elsewhere [18]. In short, between February and October 2007, 85 HIV-infected patients have been asked, and 83 participated (response rate 98%) but three patients did not complete the HADS, thus data from 80 (65 male and 15 female) patients were available for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' baseline data, rate of disclosure and support experiences in detail are published elsewhere [18]. In short, between February and October 2007, 85 HIV-infected patients have been asked, and 83 participated (response rate 98%) but three patients did not complete the HADS, thus data from 80 (65 male and 15 female) patients were available for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The current investigation uses data of a recently published study [18]. We investigated a consecutive sample of HIV-infected patients who came for routine visits to the Department of Clinical Immunology and Rheumatology at Hanover Medical School, and to the Ist Medical Department of the University Hospital, Mainz, both located in Germany.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of chronic hepatitis B, disclosure can serve as a primary prevention intervention [6][7][8]. This is particularly crucial in high endemic countries such as Ghana, where transmission of hepatitis B predominantly occurs within families as a result of exposure from mother to child [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was assumed that foreign-born patients who did not use AiMIS (1) were able to speak Japanese without an interpreter, (2) had disclosed their HIV infection to family or friends who were able to act as interpreters, or (3) refused to use a medical interpreter because they were afraid that the interpreter could breach confidentiality. One study reported that the disclosure rate of HIV was explicitly lower than that of other chronic diseases, such as viral hepatitis or diabetes mellitus [9]. Therefore, the impact of medical interpreters for patients of other chronic diseases might be more significant than for HIV patients.…”
Section: Discussionmentioning
confidence: 99%